PENGARUH MARKETING MIX TERHADAP KEPUTUSAN KONSUMEN UNTUK MENABUNG PADA BANK - Muhammad Jalari (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
The objective of the research is to find out the influence of marketing mix consisting of product, price, promotion and place, both partially and simultaneously, to consumer saving behaviour in BPR Ihuthan Ganda Kartasura, and the dominant factor that affects consumer's saving behaviour in BPR Ihuthan Ganda Kartasura The type of the research is survey research. Data collecting method is using questionaire and interview. Customers taken as samples were 50 people who have saved their funds in BPR Ihuthan Ganda Kartasura. Descriptive analysis was employed ·to support interpretation oflhe result. Multiple Regresion Analysis was used to find out the influence of marketing mix to consumers behaviour in the decision making to save their funds in BPR Ihuthan Ganda Kartasura. The result of the research shows that independent variables consisting of product (X,), price (X) promotion (:JS) and place (X,) simultaneously have significance influence to the depen dent variable ( Consumer Decision). Independent variables simultaneously have strong correlation 10 dependent variable with R = 0,270. It means that independent variables have contribution about 91 % influencing dependent variable. While 9% influenced by other variables that not included in the model.